Dari Moralitas ke Teknokrasi: Pergeseran Narasi Teknopolitik Presiden Prabowo Subianto dalam Pemberitaan Google News - Andika Sanjaya; Intan Triadini; Agustia Landra Nugraha (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This research aims to analyse how the technopolitical communication of President Prabowo Subianto's administration during the first 200 days was framed by the media through the Google News aggregator platform. Current research on presidential political communication strategies in Indonesia is only directed towards the context of social media and artificial intelligence. This research fills the gap in studies on political communication strategies mediated by aggregator platforms. Using Robert M. Entman's framing analysis with a qualitative descriptive approach, this research examines how the media frames the government's use of technology. The Entman model divides the framing process into four stages: defining the problem, diagnosing the cause, making a moral judgement, and suggesting a remedy. Data were obtained from a collection of news articles about Prabowo Subianto's administration indexed on Google News within the first 200 days of his administration. The number of news articles analysed in the study was 144 articles. The researchers divided the news into two phases: the first 0-100 days with six relevant articles and the 100-200 days phase with nine articles. The results of this study dissect the shift in Prabowo's administration narrative from a focus on morality in the first 100 days to ambitions of nuclear and digital technocracy in the following 100 days. This research underscores the narrative of the government's rise in high-level technology within the global technopolitical regime. The President has a sociotechnical imagination for various solutions to the nation's problems, even though he must face the threat of new extractivism and false reification.